Quarrying Impacts on Leaf Length, Leaf Breadth, and Leaf Area of Selected Edible Tree Plants in Quarry-Affected Areas of the Federal Capital Territory (FCT), Abuja, Nigeria - Adams, Abiodun Emmanuel (Faculty of Natural and Applied Sciences Journal of Basic and Environmental Research, 2025)
The research work assessed the impact of quarrying activities on eight (8) selected edible tree plants in terms of leaf length, leaf breadth, and leaf area, in areas around selected quarries in the Federal Capital Territory, Abuja. Direct measurement and geometrical approximation methods were among the methodologies employed to conduct the research, and this shows reductions in the leaf lengths, leaf breadths, and leaf areas at the quarry sites, compared to the control site. ANOVA and T-test at a 0.05 level of Probability were the statistical tools employed. The tests show no significant statistical differences, but findings reveal that quarrying negatively impacts the leaf length, leaf breadth, and leaf area. Dust control policies and public awareness of the negative effects of quarrying are some of the recommendations to mitigate the effects of quarrying activities on these morphological features.